Cell surface fluctuations regulate early embryonic lineage sorting - Yanagida, Ayaka; Corujo-Simon, Elena; Revell, Christopher K.; Sahu, Preeti; Stirparo, Giuliano G.; Aspalter, Irene M.; Winkel, Alex K.; Peters, Ruby; De Belly, Henry; Cassani, Davide A. D.; Achouri, Sarra; Blumenfeld, Raphael; et al. (Cell, 2022)
In development, lineage segregation is coordinated in time and space. An important example is the mammalian inner cell mass, in which the primitive endoderm (PrE, founder of the yolk sac) physically segregates from the epiblast (EPI, founder of the fetus). While the molecular requirements have been well studied, the physical mechanisms determining spatial segregation between EPI and PrE remain elusive. Here, we investigate the mechanical basis of EPI and PrE sorting. We find that rather than the differences in static cell surface mechanical parameters as in classical sorting models, it is the differences in surface fluctuations that robustly ensure physical lineage sorting. These differential surface fluctuations systematically correlate with differential cellular fluidity, which we propose together constitute a non-equilibrium sorting mechanism for EPI and PrE lineages. By combining experiments and modeling, we identify cell surface dynamics as a key factor orchestrating the correct spatial segregation of the founder embryonic lineages.
CRIS-Team Scopus Importer:2022-08-05
Keywords: cell sorting; cell surface dynamics; cell surface mechanics; embryo development; lineage segregation; morphogenesis